Miasto świateł, światła miasta czy. . . światło w mieście? Sztuczne oświetlenie w kontekście przestrzeni miejskiej = City of lights, lights of the city or. . . Light in the city? Artificial light in the context of urban space - Rosińska, Monika; Luczys, Piotr (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The history of artificial light (kerosene, eletri, LED) is at the same time the history of the origins of the urban landsape. Beginning with Benjamin`s "Passages", in whih the light brings into view the enshrouded alleys of Paris, through numerous artistic projects of the 19th and the 20th century, M. Bille`s anthropological and A. E. Stamp`s behavioural studies, ending with the onept of the intensity of light as the indiator of the metropolitan potential of a given region of the world (e.g., NASA "World Lights project"), as well as an element of the anesthetisation of urban iconosphere (e.g., light and laser design), the light is also becoming an inherent element of research within urban and spatial studies. Usually, however, the subject of light ours "additionally", "by the way", as a "supplement", and not as the primary theme, i.e., the basic line of reflection and the mutual realm of presented ideas.
Keywords: światło; przestrzeń miejska; miasto